2023
DOI: 10.1182/bloodadvances.2022009049
|View full text |Cite
|
Sign up to set email alerts
|

Most adults with severe HbSC disease are not treated with hydroxyurea

Abstract: HbSC disease is the second most frequent sickle cell disease (SCD) genotype after HbSS. Globally, approximately 55,000 newborns are delivered annually with HbSC disease, with the highest HbC gene frequency in West Africa. In Ghana, 40% of adults attending the Ghana Institute of Clinical Genetics SCD clinic have HbSC. Unlike HbSS, hydroxyurea is not routinely recommended for use in individuals with HbSC disease because of the perceived high risk benefit ratio. To test the hypothesis that at least 5% of adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Of note, hydroxyurea is not routinely recommended for patients with HbSC disease, even those with severe disease, these patients may have milder systemic disease manifestations. Further, hydroxyurea has not been formally evaluated in HbSC patients [12 ▪ ]. Given that proliferative sickle cell retinopathy has been shown to be more common in patients with HbSC disease and is by far the most common cause of vision loss in individuals with SCD, future studies are necessary to determine the efficacy of hydroxyurea in patients with HbSC disease.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…Of note, hydroxyurea is not routinely recommended for patients with HbSC disease, even those with severe disease, these patients may have milder systemic disease manifestations. Further, hydroxyurea has not been formally evaluated in HbSC patients [12 ▪ ]. Given that proliferative sickle cell retinopathy has been shown to be more common in patients with HbSC disease and is by far the most common cause of vision loss in individuals with SCD, future studies are necessary to determine the efficacy of hydroxyurea in patients with HbSC disease.…”
Section: Text Of Reviewmentioning
confidence: 99%
“…A retrospective review of 639 participant records from the Ghana Institute of Clinical Genetics, the largest SCD clinic in Ghana found that about 10% of adolescents and adults with HbSC disease had severe SCD, using the American Society of Hematology criteria, and yet 99% of those with severe disease were not on any form of diseasemodifying therapy. 7 While this may have been contextual, driven by the availability, acceptability and affordability of disease-modifying therapies in Ghana, it magnifies the disparities in disease management between SCD genotypes. Not only are there missed opportunities to manage HbSC disease effectively, but many knowledge gaps also remain.…”
Section: O M M E N T a R Ymentioning
confidence: 99%
“…Ghunney et al 1 also show us that the prevalence of HbSC disease is higher in Ghana (40%) than in the US (30%), which further underscores the urgency of addressing important questions on the options for disease-modifying therapy for this large population of patients. Interestingly, the prevalence of some HbSC comorbidities in the study by Ghunney et al (see figure ) is lower than reported in prior studies in higher-income countries 9 ; this could be a result of survival bias because many children with severe complications die before reaching adulthood in Ghana owing to a lack of early diagnosis and adoption of preventive interventions.…”
mentioning
confidence: 90%
“…In this issue of Blood Advances , the study by Ghunney et al 1 sheds light on the prevalence and severity of HbSC disease, the second most common variant of sickle cell disease (SCD), in a large cohort of patients with SCD at the Ghana Institute of Clinical Genetics SCD Clinic. The authors find that about 10.5% and 24.1% of individuals with HbSC and HbSS, respectively, were eligible for initiation of hydroxyurea based on disease severity; unfortunately, of those, less than 3% and 1%, respectively, were prescribed the drug.…”
mentioning
confidence: 99%